(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
In this article, the proficiency of higher educational institutions’ is evaluated; the quality indications of proficiency of higher educational in stitutions’ are analyzed; some approaches for improvement of proficiency of higher educational institutions’ are presented and governmental key functions in assisting this improvement are revealed.